Digital Technology Adoption in Entrepreneurs: Are Ex-Migrant Workers More Adaptive? - Jamhul Haer; Evi Gravitiani; Tetuko Rawidyo Putro (Faculty of Economic and Business, 2024)
Research Originality: Migrant workers should have improved their skills and be more adaptive to applying digital technology. This research contribution focuses on ex-migrant workers with current careers as business owners.Research Objectives: This research reviewed the determinant factor of technological adoption on entrepreneurs with the experience of ex-migrants based on some factors, such as migrant, demographic, and business.Research Methods: The applied method of this study is - logit regression analysis. This study examined 329 business owners of 1.518 workers as surveyed by the National Workforce Survey, SAKERNAS, in Mataram, in the period 2022.Empirical Results: The research result was the lower digital technology adoption of ex-migrant business owners than the non-ex-migrant workers. The causal factor was the poor educational level of ex-migrant workers in Indonesia.Implications: The empirical implication of this study is - to determine the empowerment program of ex-migrant workers regarding the digital technology utility within the scope of entrepreneurship activities and technological transfer through the ex-migrant workers of Indonesia. JEL Classification: J6, M2, O3How to Cite:Haer, J., Gravitiani, E., & Putro, T. R. (2024). Digital Technology Adoption in Entrepreneurs: Are Ex-Migrant Workers More Adaptive?. Etikonomi, 23(1), 1 – 10. https://doi.org/10.15408/etk.v23i1.34681.